Tháng Ba 1, 2024

\(\sqrt {{{\left( {2 – \sqrt 5 } \right)}^2}} – \sqrt {\frac{8}{{7 – 3\sqrt 5 }}} \). A \(- 3\) B \(- 4\) C \(- 5\) D \(- 6\)

\(\sqrt {{{\left( {2 – \sqrt 5 } \right)}^2}} – \sqrt {\frac{8}{{7 – 3\sqrt 5 }}} \).

A \(- 3\)

B \(- 4\)

C \(- 5\)

D \(- 6\)

Hướng dẫn Chọn đáp án là: C

Phương pháp giải:

Áp dụng công thức \(\sqrt {{a^2}} = |a|\)

Lời giải chi tiết:

\(\begin{array}{l}b)\;\sqrt {{{\left( {2 – \sqrt 5 } \right)}^2}} – \sqrt {\frac{8}{{7 – 3\sqrt 5 }}} = \left| {2 – \sqrt 5 } \right| – \sqrt {\frac{{16}}{{14 – 6\sqrt 5 }}} \\ = \sqrt 5 – 2 – \frac{{\sqrt {16} }}{{\sqrt {14 – 6\sqrt 5 } }}\;\;\;\left( {do\;\;2 – \sqrt 5 < 0} \right)\\ = \sqrt 5 – 2 – \frac{4}{{\sqrt {{3^2} – 2.3.\sqrt 5 + {{\left( {\sqrt 5 } \right)}^2}} }} = \sqrt 5 – 2 – \frac{4}{{\sqrt {{{\left( {3 – \sqrt 5 } \right)}^2}} }}\\ = \sqrt 5 – 2 – \frac{4}{{\left| {3 – \sqrt 5 } \right|}} = \sqrt 5 – 2 – \frac{4}{{3 – \sqrt 5 }}\;\;\left( {do\;\;3 – \sqrt 5 > 0} \right)\\ = \sqrt 5 – 2 – \frac{{4\left( {3 + \sqrt 5 } \right)}}{{{3^2} – {{\left( {\sqrt 5 } \right)}^2}}} = \sqrt 5 – 2 – \frac{{4\left( {3 + \sqrt 5 } \right)}}{4}\\ = \sqrt 5 – 2 – 3 – \sqrt 5 = – 5.\end{array}\)

Vậy \(\sqrt {{{\left( {2 – \sqrt 5 } \right)}^2}} – \sqrt {\frac{8}{{7 – 3\sqrt 5 }}} = – 5\)